Psychosocial learning environments: EFL learners’ voices during a pandemic - Bora Demir; Scott L. Walker (English Language Teaching Educational Journal, 2022)
The aim of this study was to investigate university students’ psychosocial apperceptions between face-to-face and emergency remote learning environments they experienced in the same academic term during the 2019-nCoV (coronavirus) pandemic of 2020. Utilizing a mixed methods study design, our investigation involved quantitative data collection with the DELES-TR instrument, followed by online focus group interviews with questions derived from the survey results to gain a deeper understanding of students’ perspectives of both educational environments. English as a Foreign Language students (N=687) from Çanakkale Onsekiz Mart University, Turkey participated in the study. The results indicated that students preferred the face-to-face environment over emergency remote learning due to difficulty in communication with instructors and peers and requiring students to take an active, responsible, and accountable role in their own learning in the remote learning environment.